Smart meter design for energy consumption monitoring of residential premises - Mansattha, Muhammad; Dao, Hassan; Jikaraji, Arfip (Journal of Applied Research on Science and Technology (JARST), 2023)
Electricity consumption is a crucial issue for economic development, especially in the residential sector. The number of households has increased significantly despite the declining availability of energy resources. There is a clear need for an efficient electricity consumption monitoring system that can provide accurate data on residential energy consumption. This paper proposes an Internet of Things (IoT)-based smart meter system design for monitoring household energy consumption. The system employs hardware and IoT technology, specifically the Node-MCU of ESP-32 and an ADE7757 power sensor module which runs on a 5(15) Amp of a single-phase meter. The energy consumption data is logged in cloud storage using the AppSheet platform hosted on Google Cloud. The system features digital displays and consumption analytics, allowing consumers to collect and transmit data about their energy usage. Energy usage data provides consumers accurate and timely information about their energy consumption. This information can help them better manage and reduce their energy usage. The system also offers the estimation of the energy consumption for individual appliances with a user-friendly monitoring experience for the energy sector. The proposed smart meter system has been evaluated using 1,080 data sets, with an average accuracy rate of 1.48% compared to a 5(15) Amp, single-phase meter. Additionally, the system can predict energy charges with an accuracy of 0.02% based on the schedule of residential electricity tariff regulated by the Provincial Electricity Agency (PEA), Thailand. These results show that the system is highly accurate and can promote positive user behavior towards better energy supply and demand management, reduced energy waste, and improved system reliability. The features of smart meter systems enable consumers and utilities to make more informed decisions about energy usage, promoting more efficient and sustainable energy practices.